Quick Reference Guide to Foliar Fungicides - Megan M. Dewdney (EDIS)
PP275, a 2-page illustrated fact sheet by M. M. Dewdney, provides a table of products recommended in the Florida Citrus Pest Management Guide and their effects on foliar fungal diseases, along with key guidelines for fungicide resistance management. Published by the UF Department of Plant Pathology, May 2010.